The impacts of low pay and work overload on emotional exhaustion among hotel food and beverage staff / Arnieyantie Abd Hadi ... [et al.] - Abd Hadi, Arnieyantie; Talhah, Hasiful Fatah Talhah; Md Nor, Norfezah; Mohd Karim, Nadia Liana (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Working in the hotel industry is an advantage, especially in career development. However, due to the nature of the industry, working in this sector is considered stressful because of the various factors involved, including poor pay and work overload. However, the impact of low pay and work overload on the emotional exhaustion among hotel F&B staff is still unknown and requires further research. Therefore, this study aims to ascertain how low pay and work overload affect hotel food and beverage staff's emotional exhaustion. The study involved 166 four and five-star Food and Beverage hotel staff and used a quantitative method via an online survey. The Statistical Package for the Social Sciences (SPSS) Version 21 was used to analyse the data. The emotional exhaustion of hotel food and beverage staff is significant at p<0.05, impacted by low pay and work stress. Regression analysis found that work overload, as opposed to poor pay for hotel food and beverage workers, has a greater impact on emotional exhaustion. In conclusion, to reduce emotional exhaustion among hotel food and beverage staff, management should prioritise job distribution by emphasising work delegation based on the job description, work schedule, task standard operating procedure, and employee collaboration.